Cement-Induced Irritant Contact Dermatitis: A Case Report - Natasha Caroline Gigir; Anak Agung Istri Indah Paramita; Ni Putu Devi Gema Partamayani (International Medical Journal Corp. Ltd, 2025)
Background: Irritant Contact Dermatitis (ICD) is a non-immunologic inflammatory skin reaction resulting from direct epidermal damage by exogenous agents, which subsequently activates the innate immune system. Its development is influenced by both endogenous and exogenous factors. As one of the most frequently reported occupational health problems, ICD poses a significant risk to construction workers who are routinely exposed to irritants like cement. Case Presentation: We present the case of a 35-year-old male construction worker who presented with a two-week history of intense pruritus and progressive skin thickening on his hands and feet. Dermatological examination revealed erosions, significant crusting, and marked lichenification on the dorsal aspects of both hands and feet. Management and Outcome: The patient was diagnosed with Chronic Irritant Contact Dermatitis based on his clinical history and physical findings. He was managed with a combination of systemic corticosteroids and antihistamines, complemented by topical corticosteroid therapy and comprehensive patient education. Follow-up revealed significant clinical improvement. Conclusion: The diagnosis of ICD was established through a thorough anamnesis and physical examination, highlighting the patient's occupational exposure to cement as the primary risk factor. This case underscores that effective management hinges on the strict avoidance of the causative irritant, robust patient education on personal protective equipment, and appropriate pharmacotherapy to control inflammation and symptoms.